UMIDADE E ÁGUA DISPONÍVEL NO SOLO EM MONOCULTIVO DE PASTAGEM E SISTEMA SILVIPASTORIL COM FILEIRAS DUPLAS DE EUCALIPTO (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The expansion of silvopastoral system could be achieved through reform of forage grass monoculture system in soil with a sandy surface layer, but ranchers are concerned that there may be competition for soil water between the pasture and eucalyptus. The objective of this study was to evaluate the moisture and water available in silvopastoral system and forage grass monoculture in different seasons, distance of eucalyptus trunks or terraces at 1 m depth in a Hapludox soil. Reclamation forage grass monoculture was held with cassava (2008-2010), being the eucalyptus seedlings planted simultaneously to the planting of cassava in August 2008. Two systems of terraces spaced 20 m were evaluated: a) forage grass monoculture stargrass (Cynodon nlemfuensis) system and b) silvopastoral system (2x3) +20 with stargrass forage and eucalypt tree (Eucalyptus grandis). Gravimetric moisture in the soil (θ) was determined in four seasons for eucalyptus tree had 2-3-year-old, from July/2010 to March/2011. Use the following sampling positions: 2.5, 5 and 10 m away from the stem of eucalyptus trees downstream of the terraces. Disturbed soil samples were collected at 0-0.2 m (A horizon – sandy texture), 0.2-0.4 (Bw1 – sandy loam texture), and 0.4-0.6, 0.6-0.8 and 0.8-1.0 m (Bw2 – sandy clay cloam). Field capacity and permanent wilting point waters contents was determined. The silvopastoral system compared to forage grass monoculture system decreases θ on the horizon Bw2. The θ was within the limits of the water available in the horizons A and Bw1 for the stargrass forage between the double rows of eucalyptus trees in silvopastoral system during the seasons. The silvopastoral system implemented does not compromise θ to stargrass forage at 0-0.4 m depth.